Pengaruh Online Customers Rating dan Free Shipping Promotion Terhadap Purchase Decisions yang di Mediasi oleh Brand Trust (Studi pada Pengguna Produk Sabun Pembersih Wajah Merek Gatsby pada Mahasiswa di Perguruan Tinggi Negeri di Kota – Kabupaten Serang) - Rahmatullah, Nana; Supriadi, Asep; Nupus, Hayati (CV. ITTC INDONESIA, 2025)
In the online purchasing process, consumers are often influenced by various factors, including online customer ratings and free shipping promotions. Online customer rating is one of the important factors in influencing consumer purchasing decisions, because it can provide an overview of the quality of products and services offered by sellers. Meanwhile, free shipping promotions can also influence consumer purchasing decisions. The purpose of this study was to examine the relationship between online customer ratings and free shipping promotions, as well as the mediating variable of brand trust, and purchasing decisions for facial cleansing soap products from the Gatsby brand. A quantitative method based on a descriptive approach was used in this study. This study used Purposive Sampling technique to collect data from 180 students at public universities in Serang city and district regarding their experience using Gatsby facial cleansing soap products. Using the SmartPLS 4.0 analysis tool, Structural Equation Modeling (SEM) was used for data analysis. The results of this study indicate that (1) online customer ratings have a positive and significant influence on purchasing decisions. (2) free shipping promotion has a positive and significant influence on purchasing decisions. (3) online customer ratings have a positive and significant influence on brand trust. (4) free shipping promotion has a positive and significant influence on brand trust. (5) brand trust has a positive and significant influence on purchasing decisions. (6) brand trust can moderate the effect of online customer ratings on purchasing decisions. (7) brand trust can moderate the effect of free shipping promotions on purchasing decisions